Developing Organizational Competences for Conflict Management: The Use of the Prisoner's Dilemma in Higher Education - Bruno, Andreina; Dell'Aversana, Giuseppina; Guidetti, Gloria (Frontiers in Psychology, 2018)
Interpersonal relationship require sophisticated competences of cohabitation. However, the availability of training tools to develop conflict management skills is limited and problematic. The prisoner's dilemma game (PDG), the most widely known example of game theory, a nonzero-sum game, has been used, in higher education, to provide students with an opportunity of active learning and for understanding counterintuitive concepts. It creates a condition of emotive, moral and decisional conflict in and between agents. This paper presents a case-study in higher education in which PDG was proposed to enhance organizational competences in conflict management, according to the psychoanalytic approach to organizational studies. The study aims to explore: (1) the significant characteristics of PDG used in an affective-emotional key in undergraduate classroom; (2) the learning outcomes that PDG enables to activate in the participants in relation to the development of organizational skills for conflict management. 20 students’ reflective journals were analysed using thematic analysis. Findings indicated that PDG is perceived as a useful device in students’ learning experience, which is appreciated in relation to its concreteness, intensity and debriefing phase. Learning outcomes allow new meanings about conflict, by emphasizing its defensive, automatic and interpersonal dimension. This paper contributes to the understanding of PDG as a tool to develop competences in dealing with the challenges of conflict management, since it seems to favour the overcoming of the individualistic stereotype in conflict representation by highlighting the interdependence of social interaction.